Evaluation of a massive open online course for just-in-time training of healthcare workers - Strehlow, Matthew Charles; Johnston, Jamie Sewan; Aluri, Kelly Zhang; Prober, Charles G.; Acker, Peter Corrigan; Patil, Avinash S.; Mahadevan, Aditya; Mahadevan, Swaminatha V. (Frontiers in Public Health, 2024)
Introduction: COVID-19 created a global need for healthcare worker (HCW) training. Initially, mass trainings focused on public health workers and physicians working in intensive care units. However, in resource-constrained settings, nurses and general practitioners provide most patient care, typically lacking the training and equipment to manage critically ill patients. We developed a massive open online course (MOOC) for HCWs in resource-constrained settings aimed at training bedside providers caring for COVID-19 patients. We describe the development, implementation and analysis of this MOOC.Methods: From May through June 2020, the course was developed by a multi-disciplinary team and launched on two online platforms in July. The 4-hour course comprises 6 video-based modules. Student knowledge was assessed using pre-and post-module quizzes and final exam, while demographics and user experience were evaluated by pre-and postcourse surveys and learning platform data.Results: From July 17th to September 24th, 30,859 students enrolled, 18,818 started, and 7,101 completed the course. Most participants worked in healthcare (78%) and resided in lower middle-(38%) or upper middle-(20%) income countries. Learners from upper middle-income and lower middle-income countries had higher completion rates. Knowledge gains were observed from pre-module to post-module quizzes and to final exam. Afterward, participants reported increased self-efficacy regarding course objectives, a 0.63 mean increase on a 4-point scale (95% CI [0.60,0.66]). Most participants, 93%, would recommend the course to others.This program article demonstrates the potential of MOOCs to rapidly provide access to emerging medical knowledge during a public health crisis, particularly for HCWs in high-and middle-income countries.